The Juridical Implication of Corona Virus Disease 2019 (Covid-19) Pandemic National Disaster Status Determination toward Companies Experiencing Bankruptcy - Sylvia Janisriwati (Universitas Islam Negeri Antasari Banjarmasin, 2022)
This study aims to determine the juridical implications of the juridical implication of corona virus disease 2019 (Covid-19) pandemic national disaster status determination toward companies experiencing bankruptcy. This research is a normative juridical research. In this study, the sources of legal materials used consist of 3 (three) legal materials, namely primary, secondary, and tertiary legal materials. The technique of collecting legal materials uses a literature study model using analysis of legal materials in the form of qualitative descriptive content analysis. The result of the study shows that the juridical implication of corona virus disease 2019 (Covid-19) pandemic national disaster status determination toward companies experiencing bankruptcy has implications for broad socio-economic aspects in Indonesia. In fact, the World Health Organization (WHO) as a world health organization has declared Covid-19 as a global pandemic. Furthermore, with the issuance of Presidential Decree Number 12 Year 2020 concerning the Determination of Non-Natural Disasters for the Spread of Covid-19 as a national disaster, which at the implementation level was followed up with government policies in the implementation of Large-Scale Social Restrictions (PSBB) and social distancing, which in turn led to obstruction of debtor obligations to fulfill his achievements to creditors used as a reason to defend himself against a claim for default by reason of force majeure or overmacht, this also triggers the bankruptcy of a company.